Hydrothermal decomposition of potassium feldspar under alkaline conditions. Issue 113 (3rd November 2015) - Liu, S. K.; Han, C.; Liu, J. M.; Li, H.
Abstract : For the first time, a transitional compound [Ca 2+ ≡ 2AlSi3 O8 − ≡ x OH − ] was observed for K-feldspar hydrothermal alkaline decomposition, and a model was presented. Abstract : Potassium feldspar (K-feldspar) is important for keeping ecological balance on Earth. For example, the weathering of K-feldspar generates dissolved elemental K, a necessary nutrient in soil. Recently, important developments on K-rich feldspar as an alternative potash have been reported in a broad spectrum of geographical contexts and soils. Therefore, it is a key point to understand the mechanism of extracting potassium from K-rich rocks such as K-feldspar. The "cook-and-look" experiment cannot completely elucidate the dissolution mechanism of feldspar but can provide a clear idea on physicochemical properties of K-feldspar under some extreme conditions. In this study, the reaction between feldspar and different alkalis under hydrothermal conditions was systematically investigated by combining various techniques, such as scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy, inductively coupled plasma-optical emission spectrometry, X-ray powder diffraction, and the Rietveld method. The deposition of second phases on the surface of K-feldspar was observed by SEM. The reaction process of K-feldspar and Ca(OH)2 was discussed by comparing the reaction between K-feldspar bulk and Ca(OH)2 solution with the reaction between K-feldspar and lime (CaO) powders. A transitional compound [Ca 2+ ≡ 2AlSi3 O8 − ≡ x OH − ] for KAlSi3 O8 –CaO–H2 O system was observed for the first time. Various phases appeared at different temperatures. Further, a model of K-feldspar decomposition under hydrothermal condition was presented. Studies of K-feldspar hydrothermal reaction provide important and meaningful hints on the utilization of K-feldspar as an alternative to potash, and are helpful for understanding the role of K-feldspar in keeping the ecological balance of the Earth during weathering.